PENINGKATAN KAPASITAS GURU DI ERA DIGITAL MELALUI MODEL PEMBELAJARAN INOVATIF VARIATIF - Syamsul Bahri (Yayasan Hurriah, Banda Aceh, 2021)
The purpose of this essay is to demonstrate how many new learning models may be used to empower teachers in the digital world. With a literature review, this study takes a qualitative method. Data from both primary and secondary sources was gathered, evaluated, and presented in a descriptive manner. The findings of the study show that there are four things that must be considered in order to increase teacher capacity in the digital era through one of the various innovative learning models: first, strengthening character by setting an example and strengthening habits; second, creating a digital classroom management system; third, optimizing habit formation and literacy development in the classroom and its integration into learning; and fourth, using the disc.